Hydrological Modeling in the Capluk Watershed, Rembang Regency for Evaluation of Spatial Patterns - Harini, Sri; Tjahjono, Boedi (Pusat Penelitian Lingkungan Hidup, IPB (PPLH-IPB) dan Program Studi Pengelolaan Sumberdaya Alam dan Lingkungan, IPB (PS. PSL, SPs. IPB), 2024)
Rembang Regency has little annual rainfall, ranging from 1,000 to 2,000 mm. The Capluk Watershed in Rembang is the only one with a discharge station. The average rainfall of the watershed in 2011 to 2020 is relatively low (1,877 mm/year). Moors are the dominant land use in the watershed, so the watershed is prone to drought. This study aims to assess the water balance and land use planning to reduce water deficits. The FJ Mock modeling method is used to understand hydrological phenomena, where the results can help manage water resources by regulating land use by utilizing the exposed surface parameters in the model. The results show that the demand for water in the watershed for the 2011 to 2020 period reaches an average of 49,151,012 m3/year, while the availability of water is 132,512,172 m3/year. This condition shows that the total water balance experiences an average surplus of 83,361,160 m3/year but experiences a deficit in the dry season, an average of 3,452,278 m3/year. For land use planning, scenario 5 (a combination of regionalspatial plan maps, forest area maps, general plan for forest and land rehabilitation maps, and land use in 2020) is the best in reducing the water deficit by 20,383,274 m3 or can lower the water deficit to 4,957,173 m3.